The killer toxin of Kluyveromyces lactis: characterization of the toxin subunits and identification of the genes which encode them. - Stark, M J (1986)
The killer character of the yeast Kluyveromyces lactis is associated with the presence of the linear DNA plasmids k1 and k2 and results from the secretion of a protein toxin into the growth medium. We find that toxin activity co-purifies with three polypeptides which we have termed the alpha- (mol. wt 99,000), beta- (mol. wt 30,000) and gamma- (mol. wt 27,500) subunits. The alpha-subunit appears to contain a single asparagine-linked oligosaccharide chain but neither of the smaller subunits is glycosylated. The N-terminal amino acid sequence of each subunit has been determined. Comparison of these data with the DNA sequence of plasmid k1 indicates that it encodes all three subunits. The alpha- and beta-subunits must be processed from the primary translation product of a single gene by an enzyme related to the KEX2 endopeptidase of Saccharomyces cerevisiae.